Statistical Assessment of Human Development Index Variations and Their Correlates: A Case Study of Aceh Province, Indonesia - Sasmita, Novi Reandy; Phonna, Rahmatil Adha; Fikri, Mumtaz Kemal; Khairul, Mhd; Apriliansyah, Feby; Idroes, Ghalieb Mutig; Puspitasari, Ayu; Saputra, Fachri Eka (Graha Primera Saintifika, 2024)
The Human Development Index (HDI) provides a holistic measure of human development in a country or locality. This study aims to identify factors correlated with changes in the Human Development Index and analyze changes in the distribution of the Human Development Index in Aceh Province from 2012 to 2022. Apart from the Human Development Index as the variable used in this study, five variables are used in this study as indicators: Life Expectancy, Gross Regional Domestic Product (GRDP), Per Capita Expenditure, Average Years of Schooling, and Expected Years of Schooling as socioeconomic factors. This research uses an ecological study design. Data was sourced from the